Synergetic Structural Transformation of Pt Electrocatalyst into Advanced 3D Architectures for Hydrogen Fuel Cells. Issue 51 (28th September 2020) - Kim, Jong Min; Kim, Joo‐Hyung; Kim, Jun; Lim, Youngjoon; Kim, Yongmin; Alam, Afroz; Lee, Jaeseung; Ju, Hyunchul; Ham, Hyung Chul; Kim, Jin Young
Abstract: A new direction for developing electrocatalysts for hydrogen fuel cell systems has emerged, based on the fabrication of 3D architectures. These new architectures include extended Pt surface building blocks, the strategic use of void spaces, and deliberate network connectivity along with tortuosity, as design components. Various strategies for synthesis now enable the functional and structural engineering of these electrocatalysts with appropriate electronic, ionic, and electrochemical features. The new architectures provide efficient mass transport and large electrochemically active areas. To date, although there are few examples of fully functioning hydrogen fuel cell devices, these 3D electrocatalysts have the potential to achieve optimal cell performance and durability, exceeding conventional Pt powder (i.e., Pt/C) electrocatalysts. This progress report highlights the various 3D architectures proposed for Pt electrocatalysts, advances made in the fabrication of these structures, and the remaining technical challenges. Attempts to develop design rules for 3D architectures and modeling, provide insights into their achievable and potential performance. Perspectives on future developments of new multiscale designs are also discussed along with future study directions. Abstract : 3D Pt architectures have received tremendous attention owing to their superior structure and intrinsic properties, and are suited to fuel cell electrocatalyst applications. The fabrication methods and the effect of geometry on electrochemical processes for high‐performance 3D Pt electrocatalysts are reviewed. New design guidelines for the development of such electrocatalysts are proposed, considering future research directions.